Students’ Mathematical Generalization in Solving Numeracy Problems - Naraswari, Titania Putri; Kusmayadi, Tri Atmojo; Fitriana, Laila (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Generalization is an important component of mathematical activity and has received increasing attention in school mathematics at all levels. This research aims to analyze junior high school students' mathematical generalization abilities in number pattern material. This research is descriptive research with a qualitative approach. The subjects of this research were 28 junior high school students in the even semester. The students consisted of 12 male students and 16 female students. The data collection method used is the test method. Data analysis in this research was carried out through the stages of reduction, presentation and drawing conclusions on the data obtained. Based on the results of data analysis, it shows that the mathematical generalization ability of junior high school students in number patterns was obtained: (1) 8 students (28%) had high mathematical generalization ability, (2) 15 students (54%) had medium ability, and (3) 5 students ( 18%) have low ability. These findings show that the majority of students have good mathematical generalization abilities, but there are also those who still need further assistance in improving their abilities.